2020
DOI: 10.1088/1757-899x/994/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Foundations of Water-Conducting Belt Design for Wide Coverage Sprinklers Using Numerical Simulation

Abstract: Improvement of wide-coverage sprinkler technical level requires provision of high irrigation productivity and quality with the minimum cost of construction, rational use of water and energy. It is necessary to maintain the required flow-pressure characteristics regardless of sprinkler external operating conditions and the length of the water supply belt. The article discusses the possibility of mathematical modeling application for a wide sprinkler design. The studies showed that during the calculation it is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The optimal value of the norm for watering, depending on the total number of sectors and the sector number, is determined from the expression [9,[11][12][13]:…”
Section: Methodsmentioning
confidence: 99%
“…The optimal value of the norm for watering, depending on the total number of sectors and the sector number, is determined from the expression [9,[11][12][13]:…”
Section: Methodsmentioning
confidence: 99%
“…It was found that with a specific precipitation power of 0.002-0.056 W per 1 m 2 , soil erosion is not observed, and with an increase in this indicator from 0.056 to 0.12 W/m 2 , destruction and water erosion of the soil are insignificant [10].…”
Section: Introductionmentioning
confidence: 95%
“…Studies of scientists [1][2][3][4][5][6][7][8][9][10] have established that the average intensity of rain at the beginning of the DM "Frigate" varies from 0.05 to 0.10 mm/min and reaches 0.45 mm/min at the end of the car when calm and increases to 0.6...0.8 mm/min with wind. The average actual rain intensity varies along the pipeline from 1.5 to 2.6 mm/min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplified approach was primarily due to the lack of technical and technological capabilities, appropriate digital technologies, and sensor systems. Nevertheless, modern domestic and foreign researchers have proven the relatively low effectiveness of this approach [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%